EKSEKUSI JAMINAN KREDIT NASABAH DENGAN MENGGUNAKAN BERITA ACARA PENYELESAIAN KEWAJIBAN PEMBIAYAAN PERJANJIAN PEMBIAYAAN (BAPKPPP) (STUDI KASUS PADA PT FIDERAL INTERNATIONAL FINANCE) - Jinner Sidauruk; Marthin Simangunsong (LPPM Universitas HKBP Nommensen, 2021)
Credit facilities can be provided by financial institutions (both banks and non-banks). Credit Guarantee Execution By PT. Federal International Finance Against Customers By Using Minutes of Completion of Financing Obligations of Financing Agreements (BAPKPPP), the Company has made good faith, with a maximum delay of 4 months, and the actual execution procedure of the fiduciary guarantee must be registered in the form of a certificate, so that the guarantee can be withdrawn even if it is not through a civil court process. Positive Legal Arrangements for Execution of Guarantees Against Customers Using Minutes of Completion of Financing Obligations Financing Agreements (BAPKPPP) The standard format for withdrawals is in accordance with Law No. 42 of 1999 concerning Fiduciary Guarantees, however, many leasing companies do not register their fiduciary guarantees as regulated in the Regulation of the Minister of Finance of the Republic of Indonesia Number 130/PMK.010/2012 concerning Registration of Fiduciary Guarantees.